THE ANALYSIS OF TEACHERS' LESSON PLAN IN IMPLEMENTING THEME-BASED INSTRUCTION FOR TEACHING ENGLISH TO YOUNG LEARNERS - Sesiorina, Septi (2014)
Lesson plan is an important part of instruction which consists of some aspects (Goals, Objectives, Activities, Media, and Assessments). This paper investigated what aspects taken in the lesson plan in implementing Theme-Based instruction. As many as 15 lesson plans were analyzed using qualitative method and descriptive case study as its framework. The data were obtained from document analysis and interview. Theories from Cameron (2001), Moon (2000), Brown (2001), and Richards (2001) were adapted in analyzing the documents. The results showed that both teachers were aware in making lesson plans which all aspects are connected with each other and more specifically in implementing Theme-Based, most activities have reflected the characteristics. However, improvements are needed in composing Behavioral Objectives, encouraging students' responsibility, and producing learning outcomes. Keywords: lesson plan, theme-based, young learners. Rencana Pelaksanaan Pembelajaran (RPP) adalah bagian penting dalam kegiatan belajar mengajar yang terdiri dari beberapa aspek (Indikator, Tujuan Pembelajaran, Aktivitas, Media, dan Evaluasi). Penelitian dalam skripsi ini menginvestigasi aspek apa saja yang ada dalam RPP untuk mengimplementasikan Pembelajaran Berbasis Tema. Sebanyak 15 RPP dianalisis secara kualitatif dengan kerangka studi kasus deskriptif. Data didapatkan dari analisis dokumen dan wawancara. Teori dari Cameron (2001), Moon (2000), Brown (2001), dan Richards (2001) diadaptasi untuk menganalisis dokumen. Hasil yang didapat menunjukan bahwa kedua guru dalam penelitian ini sudah paham bagaimana membuat RPP yang aspek-aspeknya saling berkaitan dan kegiatan pembelajaran sudah mencerminkan karakteristik pembelajaran berbasis tema. Namun, perlu dilakukan perbaikan dalam menyusun Behavioral Objectives, menumbuhkan sikap tanggung jawab siswa, dan menghasilkan produk pembelajaran. Kata kunci: RPP, pembelajaran berbasis tema, anak-anak.